Abraham J. (Abe) Briloff: A Biography - CRISCIONE, E. RICHARD; FOSTER, GEORGE (The Accounting Review, 2010)
Studies in the Development of Accounting Thought works to inform readers of the historical foundations on which the profession is based, the historical antecedents of today's accounting institutions, the historical impact of accounting, as well as exploring the lives and works of pre-eminent individuals in the profession's history. Recent volumes have addressed: the founders of accounting in mid-nineteenth century and the origins of the Institute of Chartered Accountants of Scotland; the life and work of accountant Stuart Chase (1888-1985), and his concerns about waste, conservation, social action, justice, ethics and fairness; and the evolving nature of accounting regulation, looking at the overwhelming number of systems and checks that practising accountants face in the wake of modern management fraud. The series is edited by Gary J. Previts, Past President of the American Accounting Association and Professor at Weatherhead School of Management, Case Western Reserve University, and Robert Bricker, Professor and Ernst & Young Faculty Fellow at Weatherhead, CWRU.